Medical emergency calls and calls for central nervous system symptoms during the COVID-19 outbreak in Hangzhou, China - Fu, Xinyan; Wang, Chunyi; Wen, Wen; Tang, Jiake; Chen, Chen; Cheng, Yongran; Zhou, Mengyun; Wu, Qi; Zhang, Xingwei; Feng, Zhanhui; Wang, Mingwei; Yu, Ping (Frontiers in Public Health, 2022)
Background: Since January 2020, the continuous and severe COVID-19 epidemic has ravaged various countries around the world and affected their emergency medical systems. The total number of emergency calls and the number of emergency calls for central nervous system (CNS) symptoms during the 2020 COVID-19 outbreak in Hangzhou, China (January 20 to March 20) were investigated, and it was investigated whether these numbers had decreased as compared with the corresponding period in 2019. Methods: The numbers of daily emergency calls, ambulance dispatches, and rescues of the Hangzhou Emergency Center (HEC) were counted. The CNS symptoms considered in this study included those of cerebrovascular diseases, mental and behavioral disorders, and other neurological diseases. Results: It was found that, during the 2020 study period, the number of emergency calls was 33,563, a 19.83% decrease as compared to the 41,863 emergency calls in 2019 (P < 0.01). The number of ambulances dispatched was 10,510, a 25.55% decrease as compared to the 14,117 ambulances dispatched in 2019 (P < 0.01). The number of rescues was 7,638, a 19.67% decrease as compared with the 9,499 rescues in 2019 (P < 0.01). It was also found that the number of emergency calls related to CNS symptoms, including symptoms of cerebrovascular diseases, mental and behavioral disorders, and other neurological diseases, was significantly reduced (P < 0.01). Conclusions: The total number of medical emergency calls and the number of emergency calls for CNS symptoms occurring in a large city in China decreased significantly during the COVID-19 epidemic.